Idiopathic pleuroparenchymal fibroelastosis – A rare idiopathic interstitial pneumonia - Balamugesh Thangakunam; Barney T.J. Isaac; Devasahayam Jesudas Christopher; Deepak Burad (Respiratory Medicine Case Reports, 2016)
Idiopathic pleuroparenchymal fibroelastosis is a rare idiopathic interstitial pneumonia. It was first described in 2004 and subsequently included in the ATS/ERS classification of idiopathic interstitial pneumonia in 2013. There have been few cases reported so far. The diagnostic criteria is still emerging and its etiology is being questioned. We report a case of pleuroparenchymal fibroelastosis probably idiopathic, the first of its kind to be reported from India, and a brief review of the literature.